REDUCING THE RISK OF NEW DRIVERS THROUGH LEGISLATION AND REGULATION - Mayhew, Daniel R. (Assurances, 1997)
Recent initiatives in Canada, the United States and elsewhere to resolve the problem of novice driver crashes have focused on driver licensing, primarily the introduction of graduate licensing which is a concept that can be traced back to the early 1970s. Several jurisdictions have already introduced graduated licensing and many others are considering doing so.The review of graduated licensing programs reveals that each of these programs is unique. Indeed, these graduated licensing programs vary substantially in their operational features — e.g., different minimum ages, a variety of conditions and restrictions that are applied in a number of different ways. Importantly, however, even given this diversity, most of these programs still remain true to basic prevention principle under conditions that minimize exposure to risk. However, there are also important similarities across programs.Finally, research results of the few evaluation studies of graduared licensing are encouraging. The experience in some jurisdictions suggests that in at least a 6 to 8% reduction in collisions.